TINDAKAN HUKUM PUBLIK : BELEIDSREGEL DINAS PERDAGANGAN DAN PERINDUSTRIAN DALAM MENGOPTIMALKAN PASAR RAKYAT TUALANG DI KECAMATAN TUALANG KABUPATEN SIAK TAHUN 2018 - Dari, Wulan; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The writing of this thesis is motivated by the researchers' views on the phenomenon in the community ofÂ  Kecamatan Tualang in the process of enforcing the Circular No. 511.2/DPP.PSR/IX/2018/200 in relocating street vendors from the edge and shoulders of the KM 4 road in front of the Tuah Serumpun Market to the Pasar rakyat tualang in 2018 viewed by using the theory of requirements that must be fulfilled in the making and application / enforcement of beleidsregels and by using the theory of factors- factors affecting law enforcement. The purpose of this thesis research is (1) to analyze the important requirements in the formation of circulars in optimizing Pasar Rakyat Tualang in 2018. (2) to analyze matters that need attention in the application or enforcement of circulars in optimizing pasar rakyat tualang in 2018. (3) to identify factors that influence the application of beleidsregels in optimizing pasar rakyat tualang in 2018. This thesis research method uses qualitative research methods. Sources of research data were taken from research informants, media and documents. Data collection techniques are done by observation, interview and document. While the data analysis technique is done by qualitative data analysis.The results of this research that the Circular no. 511.2/DPP/PSR/IX/2018/200 has fulfilled the requirements that must be met in making beleidsregels. However, in terms of application, the circular has not yet fully met the required requirements. The factors that hinder the enforcement of circulars include law enforcement factor , facilities and facilities factor, community factor and cultural factor. While legal factors do not become obstacles to the enforcement of circular.Â Keywords: Beleidsregel, Street Vendor